Preliminary investigation into subjective well-being, mental health, resilience, and spinal cord injury. (November 2013) - Migliorini, Christine; Callaway, Libby; New, Peter
Abstract : Objectives: To undertake a pilot investigation into whether individuals whose subjective well-being had returned to the normal homeostatic range after a spinal cord injury (SCI) may be more resilient and therefore, at less risk of emotional distress over time. To consider the relative stability of subjective well-being in individuals with chronic SCI whose subjective well-being had previously returned to the normative homeostatic range. Study design: Longitudinal study: Time 1 (T1) 2004 and Time 2 (T2) 2009. Setting: Victoria, Australia. Participants: Participants were adults living in the community with chronic SCI, who had no mental ill-health symptoms at T1. Outcome measures: Scales include: Comprehensive Quality of Life Scale – Adult v5 (COMQoL-A5) at T1, Personal Well-being Index (PWI – the successor to the COMQol-A5) at T2, and Depression, Anxiety & Stress Scale – short form (DASS-21) at T1 and T2. Results: Twenty-one adults participated at T1 and T2. Subjective well-being was stable for 57% of the cohort. However, 19% presented with symptoms of emotional distress by T2. There was no significant difference in age ( P = 0.94) or time since injury ( P = 0.51) between those reporting significant emotional symptoms and those without; nor was there any systematic change in health status. Conclusion: This study yielded two important findings. First, individuals with chronic SCI may be vulnerable to mental health issues even after they have previously exhibited good resilience. Second, subjective well-being after SCI may not be as stable as suggested by the general quality of life literature that have examined genetic and personality connections to subjective well-being.